Phase change energy storage wallboard with low heat conductivity and high strength as well as preparation method and application of phase change energy storage wallboard
By constructing a directional communication hole structure in cement-based materials and loading phase change materials using vacuum impregnation method, the problems of low loading efficiency and insufficient mechanical properties of phase change materials in the prior art are solved, and a phase change energy storage wall panel with low thermal conductivity and high strength are realized.
Patent Information
- Application Number
- CN202411722532.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
AI Technical Summary
Existing phase change materials have low loading efficiency in buildings and are prone to leakage during phase change. The loading method will adversely affect the mechanical properties of building materials.
The cement-based material with a directional communication hole structure was prepared by frozen casting method, and the phase change material was loaded into the holes by vacuum impregnation method to form a phase change energy storage wall panel with low thermal conductivity and high strength.
The loading efficiency of phase change materials is significantly improved, the mechanical properties and temperature adjustment capabilities of the wall panel are enhanced, the leakage of phase change materials is avoided, and the high strength and low thermal conductivity are achieved.
Smart Images

Figure CN119664045A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change energy storage media, and in particular to a low thermal conductivity and high strength phase change energy storage wallboard and a preparation method and application thereof. Background Art
[0002] In recent years, with the continuous improvement of building energy efficiency requirements, porous thermal insulation wall panels have received widespread attention. However, these wall panels have contradictory requirements between thermal conductivity and strength: although large pores can improve thermal insulation effects, they also greatly affect their mechanical properties, which limits their application range. Phase change materials, as a functional material that can regulate temperature by absorbing and releasing a large amount of latent heat during temperature changes, have received widespread attention. The application of phase change materials in the construction field can significantly reduce energy consumption, especially in areas with drastic changes in climatic conditions. Traditional research usually uses methods such as melt blending, macro-encapsulation and microencapsulation to encapsulate and shape phase change materials into building envelopes and components. Melt blending refers to the phase change material and the support material being mixed evenly and melted, and the phase change material is wrapped by a three-dimensional spatial grid structure; macro-encapsulation refers to the use of any type of container to directly seal the phase change material, which can be a tube, sphere or panel; microencapsulation refers to packaging the phase change material in a capsule made of natural or synthetic polymer materials. However, there are some problems with traditional phase change materials in practical applications: first, the loading efficiency of existing phase change materials in buildings is low; second, direct incorporation of phase change materials is prone to leakage during the phase change process, greatly weakening the energy storage effect; third, the existing loading method will have an adverse effect on the mechanical properties of building materials. Therefore, how to load phase change materials efficiently and in large quantities while maintaining high strength has become a hot topic in current research. Summary of the invention
[0003] The purpose of the present invention is to provide a phase change energy storage wall panel with low thermal conductivity and high strength and a preparation method and application thereof, so as to improve the loading efficiency of the phase change material and make the phase change energy storage wall panel have high strength and low thermal conductivity at the same time.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] On the one hand, the present invention provides a low thermal conductivity and high strength phase change energy storage wallboard, including a wallboard substrate D and a phase change material, wherein the wallboard substrate D is a cement-based material having a directional interconnected pore structure, and the phase change material is loaded in the directional interconnected pore structure.
[0006] Preferably, the cement-based material has a pore size of 10-20 μm and a porosity of 25-40%.
[0007] Preferably, the vertical thickness of the phase change energy storage wall panel is 25-50 mm.
[0008] Preferably, the phase change material is selected from any one or more of paraffin and capric acid, and the phase change material contains 0.5-1.5% by mass of FeCl3.
[0009] Further preferably, the phase change material is paraffin-FeCl3, wherein the mass percentage of FeCl3 in the paraffin is 0.5-1.5%.
[0010] Further preferably, the phase change material is decanoic acid-FeCl3, wherein the mass percentage of FeCl3 in decanoic acid is 0.5-1.5%.
[0011] Preferably, the phase change energy storage wallboard comprises the following components in parts by mass:
[0012]
[0013] Further preferably, the raw material includes the following components in parts by weight:
[0014]
[0015] Preferably, the cementitious material is selected from any one or more of Portland cement, fly ash, blast furnace slag and silica fume.
[0016] Preferably, the water reducer is selected from any one or more of polycarboxylate water reducer and lignin sulfonate.
[0017] Preferably, the modifier is selected from any one or more of polyacrylamide and bentonite.
[0018] Preferably, the early strength agent is selected from any one or more of gypsum and water glass.
[0019] In a second aspect, the present invention further provides a method for preparing the above-mentioned low thermal conductivity and high strength phase change energy storage wallboard, comprising the following steps:
[0020] S1: Mix the cementitious material, water reducing agent, early strength agent and water, add the modifier, and mix them to obtain cement paste A;
[0021] S2: pour cement slurry A into a mold with a heat conducting plate at the bottom, let it stand, and then place it on an ultra-low temperature medium for freeze casting to obtain solidified cement slurry B;
[0022] S3: thawing the solidified cement paste B to obtain a cement substrate C, and then curing the cement substrate C in a curing room for 20-32 days to obtain a wallboard substrate D having a directional interconnected pore structure;
[0023] S4: loading the phase change material into the wallboard substrate D by vacuum impregnation to obtain the wallboard substrate E;
[0024] S5: Place the wallboard substrate E in a temperature-controlled curing room for curing for 1-2 days to prepare the low thermal conductivity and high strength phase change energy storage wallboard.
[0025] Preferably, in step S1, the rotation speed of stirring and mixing the cementitious material, water reducing agent, early strength agent and water is 60±5 r / min.
[0026] Preferably, in step S1, the speed of stirring and mixing after adding the modifier is 130±10 r / min.
[0027] Preferably, in step S2, the standing time is 8-15s.
[0028] Preferably, in step S2, the ultra-low temperature medium includes liquid nitrogen.
[0029] Preferably, in step S2, only the bottom heat conducting plate of the mold is in contact with the liquid nitrogen.
[0030] Preferably, in step S2, the freeze casting time is positively correlated with the thickness of the phase change energy storage wallboard.
[0031] Further preferably, in step S2, when the thickness of the phase change energy storage wall panel is 25 mm, it needs to be frozen for 20 minutes.
[0032] Further preferably, in step S2, when the thickness of the phase change energy storage wall panel is 50 mm, it needs to be frozen for 60 minutes.
[0033] Preferably, in step S3, the thawing is slow thawing, and the slow thawing is to place the solidified cement slurry B in an environment with a temperature of 2-5°C and cure it until the ice crystals melt. The thawing time is positively correlated with the thickness of the phase change energy storage wallboard.
[0034] Further preferably, in step S3, when the thickness of the phase change energy storage wallboard is 25 mm, it needs to be thawed for 9 hours.
[0035] Further preferably, in step S3, when the thickness of the phase change energy storage wallboard is 50 mm, it needs to be thawed for 24 hours.
[0036] Preferably, step S4 includes the following steps: after placing the wall panel substrate D into a vacuum impregnation mold, turning on the vacuum pump to maintain a vacuum of 0.04-0.06 MPa, maintaining the vacuum state for 45-75 minutes, and then simultaneously spraying the phase change material through multiple phase change material inlet holes to achieve uniform spraying of the liquid phase change material on the upper surface of the wall panel substrate D, further evacuating the vacuum to 0.08-0.12 MPa, and maintaining the vacuum state for 10-12 hours.
[0037] Further preferably, in step S4, the liquid phase change material flows from the upper surface of the wallboard substrate D into the directional interconnecting channels, thereby being loaded into the wallboard substrate D.
[0038] Preferably, in step S4, the phase change material is loaded into the wallboard substrate D in an environment of 88-90°C.
[0039] Preferably, in step S4, the vacuum impregnation mold comprises an outer frame, a vacuum hole is arranged on one side of the outer frame, a bottom plate capable of feeding materials up and down is arranged inside the outer frame, a cover plate is arranged on the outer frame, and a phase change material introduction hole is arranged on the cover plate.
[0040] Further preferably, the bottom plate capable of feeding materials up and down can move up and down inside the outer frame.
[0041] Further preferably, there are a plurality of phase change material introduction holes which are evenly distributed on the cover plate.
[0042] Further preferably, when the vacuum impregnation mold is in an initial state, the bottom plate capable of feeding up and down is moved up to the top of the outer frame.
[0043] Further preferably, when the vacuum impregnation mold is in working state, the bottom plate capable of feeding up and down moves down to the bottom of the outer frame.
[0044] Preferably, in step S5, the temperature of the temperature-controlled curing room is 95-97°C.
[0045] In a third aspect, the present invention also provides an application of the above-mentioned low thermal conductivity and high strength phase change energy storage wallboard in the field of building materials.
[0046] Preferably, the phase change energy storage wall panels are suitable for green building partition walls, plateau tunnels, underground space partition panels, etc. that require temperature regulation.
[0047] The present invention uses a freeze casting method to prepare a phase change energy storage wallboard with low thermal conductivity and high strength. A directional interconnected pore structure is constructed inside the cement-based material, and the phase change material is poured through the interconnected pores. First, it overcomes the bottleneck that large sizes cannot be immersed or the amount of phase change material consumed during immersion causes waste; second, it effectively prevents the leakage of phase change materials; and third, it solves the conflicting requirements between the thermal conductivity and strength of the wallboard. Through the directional interconnected pore structure, large-scale and efficient loading of phase change materials is achieved, greatly improving the mechanical properties and temperature regulation capabilities of the wallboard.
[0048] In the present invention, the phase change material undergoes a solid-liquid phase change when absorbing heat, thereby storing thermal energy; and completes a reverse phase change when releasing heat, releasing thermal energy, thereby achieving dynamic regulation of the external temperature.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The present invention uses a cement-based material with a directional interconnected pore structure as a wallboard substrate, and loads a phase change material into the directional interconnected pore structure to prepare a low thermal conductivity and high strength phase change energy storage wallboard. The phase change energy storage wallboard has a high loading efficiency, high strength and low thermal conductivity.
[0051] (2) The present invention prepares the wallboard substrate by freeze casting, wherein the directional interconnected pore structure in the wallboard substrate has a high porosity, and a large amount of phase change material can be introduced, thereby improving the loading efficiency and energy storage efficiency of the board, and having excellent comprehensive performance.
[0052] (3) The directional interconnected pore structure constructed by the present invention has extremely strong vertical bearing capacity, which effectively solves the problem that high strength and thermal insulation cannot be achieved at the same time. The prepared phase change energy storage wallboard has high strength, low thermal conductivity and high phase change energy storage.
[0053] (4) The wallboard substrate prepared by the freeze casting method of the present invention can adjust the structural morphology of the directional interconnected pores by controlling the water-cement ratio of the cement slurry to achieve efficient introduction of phase change materials, and has the advantages of low cost, simple operation process, and easy processing.
[0054] (5) The present invention is suitable for green building partition walls, plateau tunnels, underground space partition panels, etc. that require temperature regulation, and has extremely high mechanical properties and flexible and efficient temperature regulation effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is a schematic diagram of the structure of the vacuum impregnation mold in the initial state;
[0056] Figure 2 It is a structural schematic diagram of the vacuum impregnation mold in a working state;
[0057] In the figure: 1-outer frame; 2-exhaust hole; 3-cover plate; 4-phase change material introduction hole; 5-bottom plate for feeding up and down; 6-wall panel substrate D. DETAILED DESCRIPTION
[0058] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0059] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0060] Example 1
[0061] In this embodiment, a low thermal conductivity and high strength phase change energy storage wallboard is provided, including a wallboard substrate D and a phase change material. The wallboard substrate D is a cement-based material with a directional interconnected pore structure, and the phase change material is loaded in the directional interconnected pore structure.
[0062] The low thermal conductivity and high strength phase change energy storage wallboard comprises the following components in parts by mass:
[0063]
[0064] In this embodiment, the cementitious material includes the following components in mass percentage: 70% silicate cement, 10% fly ash, 10% blast furnace slag, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically an ester polycarboxylic acid water reducer; the modifier includes the following components in mass percentage: 50% polyacrylamide and 50% bentonite; the early strength agent includes the following components in mass percentage: 50% gypsum and 50% water glass, wherein the modulus of water glass is 2.5. The phase change material is paraffin containing 1% FeCl3 by mass.
[0065] First, 200 parts of cementitious material, 0.6 parts of water reducing agent, 8 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain cement slurry A. Cement slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 60 minutes until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 2-5°C for 24 hours to obtain cement substrate C, and cement substrate C is placed in a curing room for curing for 28 days to obtain a wallboard substrate D with a directional interconnected pore structure.
[0066] The phase change material is loaded into the wallboard substrate D by using a vacuum impregnation mold. Figure 1 As shown, the vacuum impregnation mold includes an outer frame 1, a suction hole 2 is provided on one side of the outer frame 1, a bottom plate 5 capable of feeding upward and downward is provided inside the outer frame 1, a cover plate 3 is provided on the outer frame 1, and a phase change material introduction hole 4 is provided on the cover plate 3. The wallboard substrate D is placed on the bottom plate 5 capable of feeding upward and downward, and the bottom plate 5 capable of feeding upward and downward is operated to move downward to enter the working state (as shown in FIG. Figure 2 As shown), turn on the vacuum pump to maintain a vacuum of 0.05MPa, maintain the vacuum state for 60 minutes, then spray 60 parts of liquid paraffin evenly on the upper surface of the wallboard substrate D, further evacuate to a vacuum of 0.1MPa, and maintain for 11 hours. Take out the wallboard substrate D loaded with paraffin and put it into a 95°C temperature-controlled curing room for curing to constant weight, and prepare a low thermal conductivity and high strength phase change energy storage wallboard.
[0067] Example 2
[0068] In this embodiment, a low thermal conductivity and high strength phase change energy storage wallboard is provided, including a wallboard substrate D and a phase change material. The wallboard substrate D is a cement-based material with a directional interconnected pore structure, and the phase change material is loaded in the directional interconnected pore structure.
[0069] The low thermal conductivity and high strength phase change energy storage wallboard comprises the following components in parts by mass:
[0070]
[0071] In this embodiment, the cementitious material includes the following components in mass percentage: 70% silicate cement, 10% fly ash, 10% blast furnace slag, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically an ester polycarboxylic acid water reducer; the modifier includes the following components in mass percentage: 50% polyacrylamide and 50% bentonite; the early strength agent includes the following components in mass percentage: 50% gypsum and 50% water glass, wherein the modulus of water glass is 2.5. The phase change material is paraffin containing 1% FeCl3 by mass.
[0072] First, 200 parts of cementitious material, 0.6 parts of water reducing agent, 8 parts of early strength agent and 200 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain cement slurry A. Cement slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 60 minutes until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 2-5°C for 24 hours to obtain cement substrate C, and cement substrate C is placed in a curing room for curing for 28 days to obtain a wallboard substrate D with a directional interconnected pore structure.
[0073] The phase change material is loaded into the wallboard substrate D by using a vacuum impregnation mold. Figure 1 As shown, the vacuum impregnation mold includes an outer frame 1, a suction hole 2 is provided on one side of the outer frame 1, a bottom plate 5 capable of feeding upward and downward is provided inside the outer frame 1, a cover plate 3 is provided on the outer frame 1, and a phase change material introduction hole 4 is provided on the cover plate 3. The wallboard substrate D is placed on the bottom plate 5 capable of feeding upward and downward, and the bottom plate 5 capable of feeding upward and downward is operated to move downward to enter the working state (as shown in FIG. Figure 2 As shown), turn on the vacuum pump to maintain a vacuum of 0.05MPa, maintain the vacuum state for 60 minutes, then spray 60 parts of liquid paraffin evenly on the upper surface of the wallboard substrate D, further evacuate to a vacuum of 0.1MPa, and maintain for 11 hours. Take out the wallboard substrate D loaded with paraffin and put it into a 95°C temperature-controlled curing room for curing to constant weight, and prepare a low thermal conductivity and high strength phase change energy storage wallboard.
[0074] Example 3
[0075] In this embodiment, a low thermal conductivity and high strength phase change energy storage wallboard is provided, including a wallboard substrate D and a phase change material. The wallboard substrate D is a cement-based material with a directional interconnected pore structure, and the phase change material is loaded in the directional interconnected pore structure.
[0076] The low thermal conductivity and high strength phase change energy storage wallboard comprises the following components in parts by mass:
[0077]
[0078] In this embodiment, the cementitious material includes the following components in mass percentage: 70% silicate cement, 10% fly ash, 10% blast furnace slag, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically an ester polycarboxylic acid water reducer; the modifier includes the following components in mass percentage: 50% polyacrylamide and 50% bentonite; the early strength agent includes the following components in mass percentage: 50% gypsum and 50% water glass, wherein the modulus of water glass is 2.5. The phase change material is decanoic acid containing 1% FeCl3 by mass.
[0079] First, 200 parts of cementitious material, 0.6 parts of water reducing agent, 8 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in a stirring pot and mixed evenly to obtain cement slurry A. Cement slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 60 minutes until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 2-5°C for 24 hours to obtain cement substrate C, and cement substrate C is placed in a curing room for curing for 28 days to obtain a wallboard substrate D with a directional interconnected pore structure.
[0080] The phase change material is loaded into the wallboard substrate D by using a vacuum impregnation mold. Figure 1 As shown, the vacuum impregnation mold includes an outer frame 1, a suction hole 2 is provided on one side of the outer frame 1, a bottom plate 5 capable of feeding upward and downward is provided inside the outer frame 1, a cover plate 3 is provided on the outer frame 1, and a phase change material introduction hole 4 is provided on the cover plate 3. The wallboard substrate D is placed on the bottom plate 5 capable of feeding upward and downward, and the bottom plate 5 capable of feeding upward and downward is operated to move downward to enter the working state (as shown in FIG. Figure 2 As shown), turn on the vacuum pump to maintain a vacuum of 0.05MPa, maintain the vacuum state for 60 minutes, then spray 60 parts of liquid paraffin evenly on the upper surface of the wallboard substrate D, further evacuate to a vacuum of 0.1MPa, and maintain for 11 hours. Take out the wallboard substrate D loaded with paraffin and put it into a 95°C temperature-controlled curing room for curing to constant weight, and prepare a low thermal conductivity and high strength phase change energy storage wallboard.
[0081] Comparative Example 1
[0082] In this comparative example, a phase change energy storage wallboard is provided, comprising a wallboard substrate D and a phase change material, wherein the wallboard substrate D is a cement-based material having a directional interconnected pore structure, and the phase change material is loaded in the directional interconnected pore structure.
[0083] The phase change energy storage wallboard comprises the following components in parts by mass:
[0084]
[0085] In this comparative example, the cementitious material includes the following components in mass percentage: 70% silicate cement, 10% fly ash, 10% blast furnace slag, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically an ester polycarboxylic acid water reducer; the modifier includes the following components in mass percentage: 50% polyacrylamide and 50% bentonite; the early strength agent includes the following components in mass percentage: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5. The phase change material is paraffin containing 1% FeCl3 by mass.
[0086] First, 200 parts of cementitious material, 0.6 parts of water reducing agent, 8 parts of early strength agent and 70 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in the stirring pot and mixed evenly to obtain cement slurry A. Cement slurry A is poured into a mold with a heat-conducting template at the bottom, transferred to an ultra-low temperature medium for freeze casting, and frozen for 60 minutes until the block is completely solidified to obtain solidified cement slurry B. Cement slurry B is slowly thawed in an environment of 2-5°C for 24 hours to obtain cement substrate C, and cement substrate C is placed in a curing room for curing for 28 days to obtain a wallboard substrate D with a directional interconnected pore structure.
[0087] The phase change material is loaded into the wallboard substrate D by using a vacuum impregnation mold. Figure 1 As shown, the vacuum impregnation mold includes an outer frame 1, a suction hole 2 is provided on one side of the outer frame 1, a bottom plate 5 capable of feeding upward and downward is provided inside the outer frame 1, a cover plate 3 is provided on the outer frame 1, and a phase change material introduction hole 4 is provided on the cover plate 3. The wallboard substrate D is placed on the bottom plate 5 capable of feeding upward and downward, and the bottom plate 5 capable of feeding upward and downward is operated to move downward to enter the working state (as shown in FIG. Figure 2 As shown), turn on the vacuum pump to maintain a vacuum of 0.05 MPa, maintain the vacuum state for 60 minutes, then spray 60 parts of liquid paraffin evenly on the upper surface of the wallboard substrate D, further evacuate to a vacuum of 0.1 MPa, and maintain for 11 hours. Take out the wallboard substrate D loaded with paraffin and put it into a 95°C temperature-controlled curing room for curing until constant weight, and prepare a phase change energy storage wallboard.
[0088] Comparative Example 2
[0089] In this comparative example, a phase change energy storage wallboard is provided, comprising a wallboard substrate and a phase change material, wherein the wallboard substrate is a cement-based material, and the phase change material is loaded in the cement-based material.
[0090] The phase change energy storage wallboard comprises the following components in parts by mass:
[0091]
[0092]
[0093] In this comparative example, the cementitious material includes the following components in mass percentage: 70% silicate cement, 10% fly ash, 10% blast furnace slag, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically an ester polycarboxylic acid water reducer; the modifier includes the following components in mass percentage: 50% polyacrylamide and 50% bentonite; the early strength agent includes the following components in mass percentage: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5. The phase change material is paraffin containing 1% FeCl3 by mass.
[0094] First, 200 parts of cementitious material, 0.6 parts of water reducing agent, 8 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, and then 0.3 parts of modifier are placed in the stirring pot and mixed evenly to obtain cement paste A. Cement paste A is poured into a mold with a heat conductive template at the bottom to obtain cement substrate B, and cement substrate B is placed in a curing room for curing for 28 days to obtain wallboard substrate C.
[0095] The phase change material is loaded into the wallboard substrate C by using a vacuum impregnation mold. Figure 1 As shown, the vacuum impregnation mold includes an outer frame 1, a suction hole 2 is provided on one side of the outer frame 1, a bottom plate 5 capable of feeding upward and downward is provided inside the outer frame 1, a cover plate 3 is provided on the outer frame 1, and a phase change material introduction hole 4 is provided on the cover plate 3. The wallboard substrate C is placed on the bottom plate 5 capable of feeding upward and downward, and the bottom plate 5 capable of feeding upward and downward is operated to move downward to enter the working state (as shown in FIG. Figure 2 As shown), turn on the vacuum pump to maintain a vacuum of 0.05 MPa, maintain the vacuum state for 60 minutes, then spray 60 parts of liquid paraffin evenly on the upper surface of the wallboard substrate C, further evacuate to a vacuum of 0.1 MPa, and maintain for 11 hours. Take out the wallboard substrate C loaded with paraffin and put it into a 95°C temperature-controlled curing room for curing until constant weight, and prepare a phase change energy storage wallboard.
[0096] Comparative Example 3
[0097] In this comparative example, a phase change energy storage wall panel is provided.
[0098] The phase change energy storage wallboard comprises the following components in parts by mass:
[0099]
[0100]
[0101] In this comparative example, the cementitious material includes the following components in mass percentage: 70% silicate cement, 10% fly ash, 10% blast furnace slag, and 10% silica fume; the water reducer is a polycarboxylic acid water reducer, specifically an ester polycarboxylic acid water reducer; the modifier includes the following components in mass percentage: 50% polyacrylamide and 50% bentonite; the early strength agent includes the following components in mass percentage: 50% gypsum and 50% water glass, wherein the modulus of the water glass is 2.5. The phase change material is paraffin containing 1% FeCl3 by mass.
[0102] First, 200 parts of cementitious material, 0.6 parts of water reducing agent, 8 parts of early strength agent and 100 parts of water are placed in a stirring pot and mixed evenly, then 0.3 parts of modifier are placed in the stirring pot and mixed evenly, and then 60 parts of paraffin containing 1% mass fraction of FeCl3 are placed in the stirring pot and mixed evenly to obtain cement paste A. Cement paste A is poured into a mold with a heat conductive template at the bottom to obtain cement substrate B, and cement substrate B is placed in a curing room for curing for 28 days to obtain a phase change energy storage wallboard.
[0103] Referring to the national standard "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T17671-2021), the cement-based samples prepared in the above Examples 1-3 and Comparative Examples 1-3 were subjected to compression tests, and the testing instrument was a universal testing machine.
[0104] Table 1 Phase change energy storage wallboards prepared in Examples 1-3 and Comparative Examples 1-3
[0105]
[0106] It can be seen from Table 1 that compared with Comparative Examples 1, 2, and 3, the phase change energy storage wallboards prepared in Examples 1-3 have good compressive strength and flexural strength while having a higher phase change material loading rate and a lower thermal conductivity, indicating that the cement substrate with a directional pore structure obtained by the freeze casting technology of the present invention can significantly improve the loading rate of the phase change material, and on this basis, the structural morphology of the directional interconnected pores can be further regulated by controlling the water-cement ratio of the cement slurry, thereby achieving a more efficient introduction of the phase change material, thereby improving the mechanical properties and energy storage effect of the material.
[0107] In summary, the phase change energy storage wall panels prepared by the present invention solve the contradictory requirements between the thermal conductivity and strength of the wall panels, greatly improve the vertical bearing capacity of the wall panels, and significantly reduce the thermal conductivity of the wall panels. They are suitable for green building partitions, plateau tunnels, underground space partition panels, etc. that require temperature regulation, and have extremely high mechanical properties and flexible and efficient temperature control effects.
[0108] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A phase change energy storage wallboard with low thermal conductivity and high strength, characterized in that: It comprises a wallboard substrate D and a phase change material. The wallboard substrate D is a cement-based material with a directional interconnected pore structure. The phase change material is loaded in the directional interconnected pore structure.
2. A low thermal conductivity and high strength phase change energy storage wallboard according to claim 1, characterized in that: The pore size of the cement-based material is 10-20 μm, the porosity is 25-40%, and the vertical thickness of the phase change energy storage wallboard is 25-50 mm.
3. A low thermal conductivity and high strength phase change energy storage wallboard according to claim 1, characterized in that: The phase change material is selected from any one or more of paraffin and decanoic acid, and the phase change material contains FeCl3 with a mass fraction of 0.5-1.5%.
4. A low thermal conductivity and high strength phase change energy storage wallboard according to claim 1, characterized in that: The raw materials include the following components in parts by weight:
5. A low thermal conductivity and high strength phase change energy storage wallboard according to claim 4, characterized in that: The cementitious material is selected from any one or more of silicate cement, fly ash, blast furnace slag, and silica fume; The water reducer is selected from any one or more of polycarboxylate water reducer and lignin sulfonate; The modifier is selected from any one or more of polyacrylamide and bentonite; The early strength agent is selected from any one or more of gypsum and water glass.
6. A method for preparing a phase-change energy storage wallboard with low thermal conductivity and high strength as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1: Mix the cementitious material, water reducing agent, early strength agent and water, add the modifier, and mix them to obtain cement paste A; S2: pour cement slurry A into a mold with a heat conducting plate at the bottom, let it stand, and then place it on an ultra-low temperature medium for freeze casting to obtain solidified cement slurry B; S3: thawing the solidified cement paste B to obtain a cement base material C, and then curing the cement base material C in a curing room for 20-32 days to obtain a wallboard base material D having a directional interconnected pore structure; S4: loading the phase change material into the wallboard substrate D by vacuum impregnation to obtain the wallboard substrate E; S5: Place the wallboard substrate E in a temperature-controlled curing room for curing for 1-2 days to prepare the low thermal conductivity and high strength phase change energy storage wallboard.
7. The method for preparing a phase-change energy storage wallboard with low thermal conductivity and high strength according to claim 6, characterized in that: Step S4 comprises the following steps, After placing the wallboard substrate D into the vacuum impregnation mold, turn on the vacuum pump to maintain a vacuum of 0.04-0.06 MPa for 45-75 minutes, then spray the liquid phase change material evenly on the upper surface of the wallboard substrate D, further evacuate to a vacuum of 0.08-0.12 MPa, and maintain for 10-12 hours; The phase change material is loaded into the wallboard substrate D in an environment of 88-90°C.
8. The method for preparing a phase-change energy storage wallboard with low thermal conductivity and high strength according to claim 7, characterized in that: In step S4, the vacuum impregnation mold includes an outer frame, a vacuum hole is arranged on one side of the outer frame, a bottom plate capable of feeding materials up and down is arranged inside the outer frame, a cover plate is arranged on the outer frame, and a phase change material introduction hole is arranged on the cover plate.
9. The method for preparing a phase-change energy storage wallboard with low thermal conductivity and high strength according to claim 6, characterized in that: In step S5, the temperature of the temperature-controlled curing room is 95-97°C.
10. Application of the low thermal conductivity and high strength phase change energy storage wallboard according to any one of claims 1 to 5 in the field of building materials.
Citation Information
Patent Citations
Heat insulation material and preparation method thereof
CN105567175A
Cement-based material with high ion mobility as well as preparation method and application of cement-based material
CN118652085A
Thermal insulation cement-based material with directional microchannel structure and preparation method of thermal insulation cement-based material
CN118894688A
Phase-changing energy-storage composite material for building and preparation process thereof
CN1450141A
Phase-change heat storage foamed aluminum composite heat insulating wall floor
CN203334576U
Cited By
A multi-form biochar concrete structure heat preservation energy storage and humidity integrated external wall panel and a preparation method and application thereof
CN122856852A